Reliability and validity of the lactate-minimum test. A revisit - Dotan, R.; Zigel, L.; Rotstein, A.; Greenberg, T.; Benyamini, Y.; Falk, B. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: The Lactate-Minimum Test (LMT) is a high-resolution, physiologically elegant test for estimating the anaerobic threshold (AnT), or the Maximal Lactate Steady-State (MLSS). Nevertheless, it has not gained the acceptance level of typical progressive lactate-response tests (PLRT). Aim of this study was to compare LMT`s validity and reviewer reliability vs. a PLRT-type test and re-evaluate the justification for LMT`s dismissal. METHODS: Sixteen male distance trained runners (37.1±11.6 yrs) were included in the study. MLSS, LMT, and PLRT tests were performed in separate sessions. Two reviewers, blind to the subjects` identity, independently determined LMT and PLRT`s threshold velocities (VLMT, VPLRT) twice. Additionally, VLMT was determined objectively, using best-fit polynomial regressions (VLMTP). RESULTS: VPLRT, VLMT and VLMTP correlated well with VMLSS (r=0.92, 0.90, 0.93, resp.). VPLRT was identical to VMLSS (13.54 km/h), but VLMT and VLMTP were 0.33 and 0.46 km·h-1 lower, respectively. Inter-reviewer reliability was higher for VLMT than VPLRT (ICC=0.96 vs. 0.57, resp.). Intra-reviewer reliability showed a similar pattern. CONCLUSION: LMT`s underestimation of MLSS appears corrigible. The validity of corrected LMT appears comparable to that of PLRT, while its reliability, objectivity and resolution are superior. Although neither test is a perfect MLSS-substitute, the corrected LMT is not inferior to PLRT-type testing and cannot be dismissed.